Kepemimpinan Gereja Lokal dalam Pengembangan Kepemimpinan Generasi “Z” Pekerja Migran Kristen Indonesia di Malaysia - Joni Manumpak Parulian Gultom (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2022)
GenerationZ Indonesian migrant workers every year has increased the number in Malaysia. The local church in Malaysia has a big task and responsibility amid the limitations of language, culture, and leadership patterns in shaping their leadership character for God's church in the future. Even if they are migrant workers in foreign countries, they have the opportunity to become spiritual leaders of the church in the future. This study provides an update on the pastoral steps of local Malaysian churches toward the formation of leadership for Indonesian migrant workers. What is the pattern of church leadership of the local Malaysian church in the format of this GenerationZ leadership? And what strategies are used? The purpose of this research is to describe the leadership strategy of the local Malaysian church in shaping the character and leadership of Generasi Z Indonesian citizens. The research method is descriptive and qualitative. Contribution [1] to pastors and missionaries to maximize local church services in Malaysia [2] as a reference for Indonesian pastors in preparing leaders for the younger Generation of the church.[3] for the Malaysian church in outreach to incoming migrant workers. Abstrak: Pekerja migran Indonesia ke Malaysia setiap tahun mengalami peningkatan jumlah dengan prosentase terbesar berasal dari Generasierasi Z. Gereja lokal Malaysia mendapat tugas dan tanggung jawab besar di tengah keterbatasan bahasa, budaya dan pola kepemimpinan dalam pembentukan karakter kepemimpinan mereka untuk gereja Tuhan di masa mendatang. Sekalipun pekerja migran di negara asing, mereka mempunyai kesempatan untuk menjadi pemimpin pemimpin rohani gereja di kemudian hari. Penelitian ini memberikan pembaharuan kepada langkah penggembalaan gereja lokal Malaysia terhadap pembentukan kepemimpinan pekerja migran Indonesia. Pertanyaannya adalah bagaimana pola kepemimpinan pastoral gereja lokal Malaysia dalam pembentukan kepemimpinan Generasierasi Z ini? Dan strategi apakah yang digunakan? Tujuan penelitian menggambarkan srategi kepemimpinan gereja lokal Malaysia dalam pembentukan karakter dan kepemimpinan Generasi Z warga Indonesia. Metode penelitian dengan deskriptif kualitatif. Kontribusi [1] kepada gembala dan praktisi misi untuk memaksimalkan pelayanan gereja lokal di Malaysia [2] sebagai referensi bagi misionaris Indonesia dalam persiapan kepemimpinan Generasierasi muda dalam gereja.[3] bagi gereja Malaysia dalam penjangkauan pekerja migran yang datang.